The Influence of Transformational Communication, Compensation, and Work Environment on the Performance of Employees of PT. Bintang Surya Sejati Sukses Jakarta - Imam Suryono; Iggit Sulawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the influence of transformational communication, compensation, and work environment on employee performance at PT Bintang Surya Sejati Sukses Jakarta, both partially and simultaneously. Employee performance is a strategic factor in increasing the competitiveness of manufacturing companies amid global demands. This study uses a quantitative approach with a causal associative method. The sample consisted of 120 respondents, who were selected through purposive sampling from employees with a minimum working period of five years. Data was collected using Likert scale questionnaires, literature reviews, and company documents. The analysis was carried out through validity, reliability, and multiple linear regression tests using SPSS 26. The results showed that transformational communication had a positive and significant influence on employee performance, while compensation and work environment had no partial significant influence. However, these three variables simultaneously have a significant influence on performance. These findings confirm the dominant role of transformational communication in improving employee motivation, clarity of goals, and work commitment.